Critical Pedagogy and its Implementation at the UniversityofAbd Elhamid Ibn Badis University, and Mostaganem - SEDDIR, Chaimae (My University, 2020)
Raising the oppressed and marginalized learners’ awareness of their role and position in society, and encouraging them to improve their life conditions in order to participate in building a just and democratic society are the main aims of the higher education. One potential way of achieving these goals is adapting critical pedagogy as an approach of teaching. In this prospect, our foremost purpose is to investigate Mostaganem University teachers’ awareness of the meaning of critical pedagogy and its main aspects, and to examine whether the curriculum is designed according the features of that pedagogy. To accomplish this study, an interview, classroom observation and a syllabi analysis were the instruments used to collect qualitative data. The obtained data indicated that critical pedagogy is not common among the teachers and is not implemented as an approach of teaching. The study tried to put forward a set of recommendations about the importance of implementing critical pedagogy aspects in teaching learners.
Keywords: Oppressed; Marginalized; Awareness; Democratic society; Critical pedagogy; Education